2001
DOI: 10.1159/000055121
|View full text |Cite
|
Sign up to set email alerts
|

New Drugs in the Palliative Chemotherapy of Advanced Non-Small-Cell Lung Cancer

Abstract: In inoperable advanced non-small-cell lung cancer (NSCLC), palliative chemotherapy is established and aims at palliation of symptoms, improvement of quality of life and prolongation of survival. In the last years, several new drugs with enhanced activity towards NSCLC and improved toxicity profile have been characterised, for example vinorelbine, gemcitabine, paclitaxel and docetaxel. Data from randomised trials suggest that regimens containing new drugs are more active than older combinations. Platin-based co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2005
2005

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…In case the null hypothesis has to be rejected after the statistical test (P<0.05) it is concluded that one of the groups is superior to the others in terms of success rate. In case of the noninferiority approach, the null hypothesis states that one (14) 85 (10) Duration of surgery (min) 58 (11) 58 (13) 57 (13) group is inferior to the other. When this null hypothesis is rejected (P<0.05) then the alternative hypothesis, namely that the groups are not inferior to each other, becomes more probable.…”
Section: Discussionmentioning
confidence: 99%
“…In case the null hypothesis has to be rejected after the statistical test (P<0.05) it is concluded that one of the groups is superior to the others in terms of success rate. In case of the noninferiority approach, the null hypothesis states that one (14) 85 (10) Duration of surgery (min) 58 (11) 58 (13) 57 (13) group is inferior to the other. When this null hypothesis is rejected (P<0.05) then the alternative hypothesis, namely that the groups are not inferior to each other, becomes more probable.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the critical issues of care in these patients are palliation and quality of life (QoL). Second-line chemotherapy of cisplatin-refractory tumors should consist of non-platinum-containing regimens [2]. The highest single-agent activities in this group of drugs have been reported for paclitaxel (42% objective response, OR) [3] and gemcitabine (28-38% OR) [4,5].…”
Section: Gemcitabine Monotherapy As Second-line Treatment In Cisplatimentioning
confidence: 99%
“…Survival at 5 years is about 5% in patients with N2 disease (involvement of ipsilateral or subcarinal mediastinal lymph nodes or ipsilateral supraclavicular lymph nodes), and 50% in patients with T3 disease (tumor involving the pleura, chest wall, diaphragm, or pericardium) without lymph node involvement. Patients with N3 (contralateral mediastinal hilar or supraclavicular lymph node involvement) or T4 tumors (invasion of mediastinal organs, malignant pleural effusion) are treated with palliative intent (Malayeri et al, 2001). Postoperative mediastinal radiation therapy has been shown to significantly reduce the risk of local relapse with no or little impact on survival (PORT Meta-analysis Trialists Group, 1998), while adjuvant chemotherapy is ineffective (Souquet and Geriniere, 2001).…”
Section: Clinical Relevance and Management Of Nonsmall Cell Lung mentioning
confidence: 99%